Study the Functional VNTR Polymorphism of Monoamine Oxidize a (maoa) Gene in Violent Criminal Behavior for Iraqi Prisoners - Suhad Redah AL-Tayie (Journal of Global Pharma Technology, 2017)
Monoamine oxidise A (MAOA) enzyme activity is changed in mood disorders and lower activity associated with criminal and aggressive behaviours. The monoamine oxidise-A (maoa) gene, which plays a vital role in degradation of neurotransmitters such as serotonin, nor epinephrine, and dopamine, contains a polymorphism in its promoter region that affects transcriptional efficiency. maoa -VNTR genotype has been related with both psychological and physical measures. Blood samples were provided from 200 prisoners (case group) who convicted with terrorism (150 sample), murder (30 sample) and drug trading (20 sample) issues selected from Al –Hila prison reformist central for men and women / Babylon city and from position and deporting division /Karbala, this sample include (160 male and 40 female).Additionally, control subject (100) sample were provided included (54 male and 46 female). DNA was extracted and the mentioned polymorphism (VNTR) was genotyped by PCR. The results were confirmed by using sequencing technique. The maoa VNTR polymorphism was analyzed in male and female separately due to the gene location on X-chromosome .The results demonstrated that there was non- significant difference observed between all genotypes and alleles frequencies between case and control male (p> 0.05),whereas in female a significant association in 3.5/3.5 and 5.5/4.5 genotypes (p<0.01) ,additionally the 3.5 R alleles was associated with higher risk of violent criminal behavior in female (p= 0.004; OR=2.62; 95% CI=1.36-5.05). The maoa genotype 3.5/3.5 and the risk allele were a significantly associated within female and they might be associated with increased risk of engaging in violent crimes.Keyword: Monoamine Oxidase- A, Maoa- VNTR, Genotype, Violent criminal behavior.